Tinjauan Normatif Terhadap Kewenangan Penyelidikan dan Penyidikan Tindak Pidana Korupsi oleh Komisi Pemberantasan Korupsi dan Kepolisian Republik Indonesia - Muflihah, Rifa; , Sudaryono, S.H., M.Hum (2017)
This study aims to determinate the authority by law enforcement officials in the institutions of the Corruption Eradication Commission (KPK) and the Indonesian National Police (Polri) in terms of the research and the investigation of corruption. This study uses normative legal approach. Data collection techniques in this research is the study of literature and analyzed by qualitative data analysis, which analyzes legislation relating to powers of inquiry and investigation by the Commission and the National Police. These results indicate that (1) the Commission and the Police have the authority to conduct inquiries and investigations of corruption, but the Commission is not allowed to monopolize penyelidikandan investigation. (2) setting the coordination and supervision contained in Law No. 30 of 2002 on the Corruption Eradication Commission which states that the coordination of the Commission as coordinator for other institutions, and in the supervision of the Commission the right to conduct surveillance measures and the specific reasons the Commission is entitled to take over the investigation and a previous investigation or have been conducted by the police. Keywords: Research, Investigations, Corruption